2002
DOI: 10.1093/aob/mcf089
|View full text |Cite
|
Sign up to set email alerts
|

Early Ovule Development Following Self- and Cross-pollinations in Eucalyptus globulus Labill. ssp. globulus

Abstract: The study was conducted to identify the self-incompatibility mechanism in Eucalyptus globulus ssp. globulus. Controlled self- and cross-pollinations were conducted on individual flowers from three mature trees that had self-incompatibility levels of 76, 99.6 and 100%. Flowers were harvested at 4, 6 and 8 weeks after pollination. Embryology was investigated by bright field microscopy on material harvested at 4 and 6 weeks after pollination. Fertilization had taken place at 4 weeks after pollination with zygotes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
28
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 31 publications
(30 citation statements)
references
References 18 publications
2
28
0
Order By: Relevance
“…One locule from all flowers harvested at 2, 4 and 6 weeks after pollination was fixed in 3% glutaraldehyde as described previously (Pound et al 2002b). Following fixation, some locules were processed further, including one locule from three self-and crosspollinated flowers from three trees harvested 2 weeks after pollination, and one locule from a single self-and cross-pollinated flower from the same trees harvested 4 weeks after pollination.…”
Section: Field Harvests and Microscopy Workmentioning
confidence: 99%
See 2 more Smart Citations
“…One locule from all flowers harvested at 2, 4 and 6 weeks after pollination was fixed in 3% glutaraldehyde as described previously (Pound et al 2002b). Following fixation, some locules were processed further, including one locule from three self-and crosspollinated flowers from three trees harvested 2 weeks after pollination, and one locule from a single self-and cross-pollinated flower from the same trees harvested 4 weeks after pollination.…”
Section: Field Harvests and Microscopy Workmentioning
confidence: 99%
“…Following fixation, some locules were processed further, including one locule from three self-and crosspollinated flowers from three trees harvested 2 weeks after pollination, and one locule from a single self-and cross-pollinated flower from the same trees harvested 4 weeks after pollination. The ovules from these samples were dehydrated, embedded in glycol methacrylate, serially longitudinally sectioned and stained as described in Pound et al (2002b). The remaining intact fixed locules were dehydrated through methoxy-ethanol to ethanol and stored for observation.…”
Section: Field Harvests and Microscopy Workmentioning
confidence: 99%
See 1 more Smart Citation
“…There was no difference between self-and cross-pollination in pollen tube growth and fertilized ovules for Eucalyptus regnans . For E. globulus, there were more healthy, fertilized ovules from cross-compared to self-pollination, and the mechanism of self-incompatibility appeared to have both late pre-and postzygotic components (Pound et al 2002a). Another study to investigate the site of action of incompatibility found no difference in number of pollen tubes in the style (prezygotic) but, in contrast, almost complete lack of self-seed production (post-zygotic) compared with cross-pollinated seed (Pound et al 2002b).…”
Section: Introductionmentioning
confidence: 98%
“…The degree of self-incompatibility is illustrated by the index of self-incompatibility 24 . Normally, in self-incompatible and selfcompatible plants, the index of self-incompatibility is greater than 80% and less than 50%, respectively 37 . In self-incompatible plants, self-pollination lowered the seed-setting rate 16 whereas cross-pollinated plants gave a higher fruit setting rate 35,36,38,39 .…”
Section: Self-incompatibility Testmentioning
confidence: 99%